Disseminated nocardiosis during systemic steroid therapy for the prevention of esophageal stricture after endoscopic submucosal dissection. Issue 3 (3rd November 2014) - Ishida, Tsukasa; Morita, Yoshinori; Hoshi, Namiko; Yoshizaki, Tetsuya; Ohara, Yoshiko; Kawara, Fumiaki; Tanaka, Sinwa; Yamamoto, Yuki; Matsuo, Hiroo; Iwata, Kentaro; Toyonaga, Takashi; Azuma, Takeshi
<x xml:space="preserve">Abstract</x> An 85‐year‐old man underwent endoscopic submucosal dissection for a large superficial esophageal epithelial neoplasm, which required removal of 95% of the circumference of the esophageal mucosa. Steroids were given orally to prevent esophageal stricture starting on day 3 postoperatively. In the 6th week of steroid treatment, he developed high fever without other symptoms. Chest computed tomography revealed a nodular lesion in the lung. Sputum sample showed Gram‐positive, branching, filamentous bacteria, and a diagnosis of nocardiosis was suspected. Brain magnetic resonance imaging revealed multiple focal lesions which indicated dissemination of nocardiosis. Trimethoprim‐sulfamethoxazole was immediately started, which led to the disappearance of pulmonary and cerebral nocardiosis with alleviation of fever. Recently, oral steroid treatment has been widely used for the prevention of esophageal stricture. However, the present case indicates the risk of life‐threatening infection and the importance of close monitoring of this treatment.